The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cells10092363
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Polymorphism of the Subchloroplast—Granum and Stroma Thylakoid Membrane–Particles. II. Structure and Functions

Abstract: In Part I, by using 31P-NMR spectroscopy, we have shown that isolated granum and stroma thylakoid membranes (TMs), in addition to the bilayer, display two isotropic phases and an inverted hexagonal (HII) phase; saturation transfer experiments and selective effects of lipase and thermal treatments have shown that these phases arise from distinct, yet interconnectable structural entities. To obtain information on the functional roles and origin of the different lipid phases, here we performed spectroscopic measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…The addition of 20 U mL −1 WGL further suppressed the isotropic phases and diminished the L and H II phases; at 100 U mL −1 of WGL, all phases were eliminated ( Figure 6 ). These data are in good agreement with our previous results on isolated granum and stroma sub-chloroplast TM particles [ 38 , 39 ]. It is important to note that 5 U mL −1 WGL, even over long incubation times, did not disturb the structure and function of TMs; it did not increase the permeability of the membranes and exerted no effects on the excitation-energy distribution in the TMs, on the activity of PSII, nor the pattern and macro-organization of PPCs ( Figure S4 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The addition of 20 U mL −1 WGL further suppressed the isotropic phases and diminished the L and H II phases; at 100 U mL −1 of WGL, all phases were eliminated ( Figure 6 ). These data are in good agreement with our previous results on isolated granum and stroma sub-chloroplast TM particles [ 38 , 39 ]. It is important to note that 5 U mL −1 WGL, even over long incubation times, did not disturb the structure and function of TMs; it did not increase the permeability of the membranes and exerted no effects on the excitation-energy distribution in the TMs, on the activity of PSII, nor the pattern and macro-organization of PPCs ( Figure S4 ).…”
Section: Resultssupporting
confidence: 93%
“…In our earlier studies, we established correlations among the variations in the temperature, pH, and osmotic and ionic strengths of the medium as well as the activity of VDE and the phase behavior of the bulk lipid molecules [ 31 , 36 , 37 ]; we also clarified that isolated grana and stroma lamellae contain all the three non-bilayer phases [ 38 ]. Analyses of our structural and functional data strongly suggested that the isotropic phases originate from membrane fusions and junctions [ 39 ] and from VDE: lipid assemblies [ 31 ]. (Note that in model membranes, VDE: lipid structures form an H II phase [ 40 ].)…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lipocalin-non-bilayer lipid structures may rejoin the bilayer membrane network of TM or IMM when the remodelling and extension of the membrane network occurs. Isolated granum and stroma TMs placed in a proper aqueous environment spontaneously form extended and interconnected membrane networks made of narrow membrane channels rich in proteins embedded in the bilayer membrane [30]. Thus, DEM proposes the coexistence of the bilayer and non-bilayer phases in the TM and IMM and serves to explain the dynamic homeostasis of the energy-transducing membranes in which the equilibrium may shift towards the bilayer or non-bilayer phase depending on the energy needs of cell [9].…”
Section: Introductionmentioning
confidence: 99%